68 Managing the Informal Sector Workforce of the Social Security System in a Selected Municipality in the Eastern Region of Thailand - Yordmanee, Somanat; Prammanee, Noppadol; Tubsree, Chalong (HRD Journal, 2013)
The purposes of this study were: 1) to develop a system to manage the informal sector in the workforce; 2) to investigate the informal sector’s understanding of their rights and capacities; 3) to study the needs of the informal sector in terms of paying social security premiums; and 4) to evaluate the developed system. The researcher developed a one-stop service system to manage the informal sector in the selected workforce. The researcher’s methodology was research and development (R&D). The development process of the study was the ADDIE model which is Analysis, Design, Develop, Implement and Evaluation. The one-stop service system was implemented and evaluated by the stakeholders. A purposive sample was selected, composed of 29 stakeholders who lived in a selected municipality in the Eastern region of Thailand. The data were collected by conducting a semi-structured interview. The results of this study showed that most of the participants in the selected municipality in the eastern part of Thailand knew their rights and they could have to pay premiums of up to 200 baht monthly. They expressed moderate satisfaction with the overall system, but commented that the self-service subsystem was too difficult for the informal sector, and it should be better and faster than the present service. They concluded that the system would be more useful if it was easier to use. Keywords : Informal Sector, Management, System, Social Security, Municipality, Thailand